Resiliensi dan altruisme pada relawan bencana alam - Melina, Gloria Gabriella; Grashinta, Aully; Vinaya, Vinaya (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2012)
Indonesia is among countries that are vulnerable to natural disasters. Volunteer is someone who has a desire to help others without expecting reward or known as altruism (Myers, 1999). If you see the volunteers, which is expected of individuals who have the capacity to survive even in a difficult situation in a state of disaster. Capacity is referred to as resilience (Maddi & Khoshaba, 2005). Therefore, this study aims to determine the relationship between altruism with resilience. Participants in this study were 100 volunteers who are members of an Non Government Organization (NGO). Methods of data collection use a scale of resilience and altruism. By using a quantitative approach and the concept of descriptive correlation study Pearson product moment correlation, the result showed that there is a positive and significant correlation between resilience and altruism (r = .448, p < .01) of volunteer. This is means that the higher the resilience, the higher the altruism, vice versa, the lower the resilience, the lower the altruism that is owned by a natural disaster volunteer.